The impact of US macroeconomic news announcements on Chinese commodity futures. Issue 12 (1st December 2020) - Cai, Haidong; Ahmed, Shamim; Jiang, Ying; Liu, Xiaoquan
Abstract : Using intraday data from 2013 to 2016, we examine the instantaneous response of eight Chinese commodity futures to 19 different types of scheduled US macroeconomic news announcements after the introduction of night trading in China. We provide robust evidence that the surprise components of a number of news announcements exhibit a significant effect on returns, trading volume, and volatility of a majority of Chinese futures contracts, with gold and silver futures being the most sensitive. Moreover, we observe an asymmetric effect between positive and negative surprise components. A further examination of the responses to the US macroeconomic news announcements using US gold and silver futures over the same sample period provides qualitatively similar results with larger magnitudes. This evidence suggests a possible channel through which the impact of macroeconomic news announcements transmits from the US to the Chinese commodity futures market.